Workshop Report. DeRISK SE Asia: Project results and experience sharing event in Vietnam - Le Thi Tam; Nguyen Mai, Huong; Trinh Thanh Ha; Vu Huong, Ngan; Swaans, Cornelis P.M. (2022)
This report summarizes the experience sharing and lessons learned from the implementation of DeRISK SE Asia in Vietnam. The outcomes and legacy generated from the project continue in Vietnam through the CGIAR Initiative on Asian Mega Deltas particularly transitioning to Digital Climate Advisory and Bundled Services (DCAS+).